Pemilihan jenis pohon untuk pengembangan arboretum Kampus IV Universitas Khairun - Kurniawan, Andy; Ashari, Reyna; Salatalohy, Asiah; Marasabessy, Much Hidayah (Universitas Khairun, 2023)
Arboretum is an artificial forest that collects various types of plants for educational purposes and plant preservation. The development of an arboretum requires basic information on environmental conditions and tree species suitable for planting. Therefore, this study was carried out with the aim of selecting tree species for the development of the arboretum at Campus IV, Khairun University. The research was carried out at Campus IV of Khairun University which included a study of land conditions, a literature review of local tree species, and tree species selection. A potential location for an arboretum is the triangular park at the campus entrance. This location was planted with the Angsana species (Pterocarpus indicus) in 2019, which has now grown to the pole and tree stage with an average height of 6 m and an average crown diameter of 4.1 m. The soil has a clay texture with a pH of 5.2 and humidity of 55%. Thus, the location can be planted with intolerant tree species on the edges and tolerant species in the middle which has been shaded by angsana vegetation. The tree species selected for species enrichment in the arboretum are local species in the Wallacea region, namely Canarium indicum, Palaquium spp., Syzygium malaccense, Vitex cofassus and Diospyros celebica; timber wood-producing species, namely Swietenia macrophylla and Ochroma pyramidale; producer of gaharu NTFPs, namely Aquilaria malaccensis; and shade-tree for aesthetics, namely Tabebuia rosea.